Systems, Software and Services Process Improvement : 26th European Conference, EuroSPI 2019, Edinburgh, UK, September 18-20, 2019, Proceedings /: 26th European Conference, EuroSPI 2019, Edinburgh, UK, September 18-20, 2019, Proceedings. (2019) - Unknown
No abstract available